The Scribal Witness: Narrative Authority in Ancient Chinese Literature - Crone, Thomas (Early China, 2023)
The scribe has been granted a special role in the creation of ancient Chi¬nese narrative prose. Many texts seem to imply the presence of his person or written records, and scholars have often treated this feature as an indication of authorship. In this paper, I argue that another way of relating the scribe to ancient Chinese narrative prose is to see in him not an author but a witness of the events told. I will use several examples to demonstrate that the figure of the scribe stands out by its function of authenticating the narratives in which scribes takes part. Moreover, occasionally scribes appear to have been added to pre-existing "scribe-less" narratives. I will conclude my discussion by detailing how these findings shed light on the composition of individual pieces of literature and the nature of ancient Chinese narrative writing in general.
CRIS-Team Scopus Importer:2023-08-11